Improving Maternal and Reproductive Health in South Asia : Drivers and Enablers - El-Saharty, Sameh; Chowdhury, Sadia; Ohno, Naoko; Sarker, Intissar (Washington, DC: World Bank, 2016)
South Asia Region (SAR) has decreased maternal mortality ratio (MMR) by 65 percent between 1990 and 2013, which was the greatest progress among all world regions. Such achievement implores the question, What made SAR stand out against what is predicted by standard socioeconomic outcomes?